The Albanian cause in the politics of Russia at the turn of 19/20th centuries - Giza, Antoni (Balcanica Posnaniensia. Acta et studia, 1999)
The article is devoted to Russia’s attitude toward the Albanian question at the turn of the nineteenth and twentieth centuries in the context of great-power rivalry and national conflicts in the Balkans. The research problem concerns the influence of Russian Balkan policy on the development of the Albanian national movement and on the relations of Albanians with Serbia, Montenegro, and the Ottoman Empire. The aim of the study is to show Russian policy toward Albanian national aspirations and territorial conflicts in the Balkans. The author employs a historical-political method, analyzing diplomatic documents, the press, and political literature. The article demonstrates that Russia consistently supported Serbia and Montenegro, often at the expense of Albanian interests, treating the Albanians as an obstacle to Pan-Slavic plans in the Balkans. The article discusses the development of Albanian national consciousness, the activity of the Albanian League, and conflicts over Kosovo and access to the Adriatic. The author emphasizes that the Albanian national movement developed in parallel with the weakening of the Ottoman Empire and the growing threat posed by Slavic states. The results of the analysis indicate that Russian policy toward Albania was subordinated to strategic Pan-Slavic interests and the desire to strengthen Russian influence in the Balkans.